GUIDELINES OF ACADEMIC AFFAIRS ADMINISTRATION IN DIGITAL ERA OF RATSADA SCHOOL UNDER THE SECONDARYEDUCATIONAL SERVICE AREA OFFICE TRANG KRABI - Jongmee , Natthida; PhrakhruPhichitsuphakan; Weerapornkan, Boonlert (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed 1) to study the condition of academic administration at Ratsada School, 2) to study the guidelines for academic administration in the digital era at Ratsada School, and 3) to present the guidelines for academic administration in the digital era at Ratsada School. It is a qualitative research by in-depth interviews with stakeholders. 15 Interviewed 5 experts Group discussion with 7 experts. The research tools were in-depth interviews, group discussions, and data analysis by analyzing content based on interviews and group discussions. The results of the study were as follows: 1) The condition of academic administration of Ratsada School was found that (1) the curriculum part, the administrators systematically promoted the development of the school curriculum. All stakeholders actively participated with dedication and engagement in the process, ensuring that the curriculum aligns with the school's context and effectively enhanced students' full potential. (2) Teaching and learning management part, teachers employed diverse instructional methods, resulting in students achieving higher academic performance than the school's target benchmarks. (3) Measurement and evaluation part, there was a management system for developing and improving assessment tools, and the results from evaluations were utilized for administrative purposes. (4) Follow up and supervision part, there was support for teachers' work and collaboration, enhancing the quality of their tasks to ensure efficiency. 2) Academic administration guidelines in the digital age at Ratsada School included (1) Curriculum development part, the curriculum must be revised to align with evolving learning needs, starting with an analysis of the requirements related to curriculum development. (2) Teaching and learning management part, teaching and learning must be student-centered type to encourage participation and develop students' analytical thinking skills. (3) Measurement and evaluation part, assessment was conducted at every educational level, and assessment tools were developed through a digital system. (4) Follow up and supervision part, the use of technology in managing supervision and monitoring work was essential for improving the quality of education. 3) Presentation of academic administration guidelines in the digital era at Ratsada School. It was found to be feasible, appropriate and useful for use in academic administration in the digital age of Ratsada School under the Trang Secondary Educational Service Area Office, Krabi.